Pengaruh Motivasi dan Penempatan kerja terhadap Kinerja Guru - Yusup Supriadi; Aditya Yudanegara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Teacher performance in an educational institution is the result of the quality, quantity, responsibility, cooperation, and initiative achieved by teachers in carrying out their duties in accordance with the responsibilities given to them. Teacher performance does not always meet expectations or desires; it fluctuates. Motivation and job placement are some of the factors that influence performance. The purpose of this study was to determine the effect of motivation and job placement on teacher performance. The research method used was descriptive verification. The unit of analysis was ASN teachers at SMK Negeri 1 Sukalarang, Sukabumi Regency. The sample was determined using a sampling technique.non-probabilitySampling with saturated sampling (census). Data collection was carried out using questionnaires and through observation. Statistical tests in this study used correlation and regression analysis. The results of the partial t-test showed that motivation had no significant effect on teacher performance, while the job placement variable had a positive and significant effect on teacher performance partially. The results of the f-test showed that both variables (motivation and job placement) simultaneously influenced teacher performance. This indicates that teacher performance will be more optimal if supported by good work motivation and job placement that is in accordance with teacher competencies.